Effects of intraoperative positive end-expiratory pressure optimization on respiratory mechanics and the inflammatory response a randomized controlled trial - Ruszkai Zoltán (JOURNAL OF CLINICAL MONITORING AND COMPUTING, 2021)
Applying lung protective mechanical ventilation (LPV) during general anaesthesia even in patients with non-injured lungs is recommended. However, the effects of an individual PEEP-optimisation on respiratory mechanics, oxygenation and their potential correlation with the inflammatory response and postoperative complications have not been evaluated have not been compared to standard LPV in patients undergoing major abdominal surgery. Thirty-nine patients undergoing open radical cystectomy were enrolled in this study. In the study group (SG) optimal PEEP was determined by a decremental titration procedure and defined as the PEEP value resulting the highest static pulmonary compliance. In the control group (CG) PEEP was set to 6 cmH2O. Primary endpoints were intraoperative respiratory mechanics and gas exchange parameters. Secondary outcomes were perioperative procalcitonin kinetics and postoperative pulmonary complications. Optimal PEEP levels (median = 10, range: 8-14 cmH2O), PaO2/FiO2 (451.24 ± 121.78 mmHg vs. 404.15 ± 115.87 mmHg, P = 0.005) and static pulmonary compliance (52.54 ± 13.59 ml cmH2O-1 vs. 45.22 ± 9.13 ml cmH2O-1, P < 0.0001) were significantly higher, while driving pressure (8.26 ± 1.74 cmH2O vs. 9.73 ± 4.02 cmH2O, P < 0.0001) was significantly lower in the SG as compared to the CG. No significant intergroup differences were found in procalcitonin kinetics (P = 0.076). Composite outcome results indicated a non-significant reduction of postoperative complications in the SG. Intraoperative PEEP-optimization resulted in significant improvement in gas exchange and pulmonary mechanics as compared to standard LPV. Whether these have any effect on short and long term outcomes require further investigations. Trial registration: Clinicaltrials.gov, identifier: NCT02931409.